IDENTIFIKASI DAYA TAMPUNG BEBAN PENCEMARAN SUNGAI CIUJUNG DENGAN MODEL WASP DAN STRATEGI PENGENDALIANNYA - Hindriani, Heny (Bumi Lestari; Vol 13 No 2 (2013), 2013)
Abstract Crucial Issues at the downstream Ciujung river is the increasing load of water pollution. BOD is one of the water pollution indicator in the stream. This study aimed to determine the amount of Total Maximum Dailly Load (TMDL)in Ciujung River as a basis for determining river pollution control strategies. TMDL of BOD determined by modeling WASP (Water quality Analysis Simulation Program) and the results were compared with the standar streams due to PP No.82/2001. Water pollution control strategies of Ciujung River determined by analysis of the results of an expert survey method with AHP (Analytical Hierarchy Process). The results showed that the water quality of Ciujung rivers at minimum reliable discharge meets the river standard of 4th class along the 13.5 km. Simulation results at maximum reliable discharge and reduction of point source pollution load by 90% indicates that the water quality in the segment Nagara to Tirtayasa (27.5km) can meet the 4th class of river quality standard with average TMDL 21,241.74 kg/day. whereas downstream areas, which do not meet 4th class of quality standards along 4.5 km. Alternative strategies of Ciujung rivers water pollution control with the aim of reducing the pollution load is tightening licensing waste disposal (eigen value 0.260).
Keywords: Keywords : Ciujung River, TMDL, WASP, AHP